Labyrinth of lies - Hannon, Irene (Hannon, Irene. Triple threat, 2021)
"Detective Cate Reilly and former colleague Zeke Sloan-the man who once stole her heart-are reunited when she goes undercover at an exclusive girls' school and discovers that no one is who they seem to be . . . and danger waits at every turn"--